DANGEROUS HEAVY METAL POLLUTION AND NITRATE AND PHOSPHATE CONCENTRATION CONTAINED IN THE SEAWEED THALLUS (Kappaphycus Alvarezii and Gracilaria Verrucosa) - Zakirah Raihani Ya’la,Ali Husni , Tri Joko Santoso, Triyani Dewi , Marhawati, Maemunah, Eka Rosyida, Samliok Ndobe, Faisal Haris (Chelonian Research Foundation, 2024)
Kappaphycus alvarezii seaweed is a key local commodity in Central Sulawesi. However, since 2012, its production has drastically decreased, especially in mining exploration centers such as the coastal waters of Morowali Regency and Palu Bay. Mining activities, including nickel mining in Morowali, gold mining in Poboya, and other mining operations in Palu, have led to changes in land use, transforming areas into mining concessions. This situation raises significant concerns as both mining commodities and seaweed are crucial regional assets for driving the local and national economy. Mining activities have resulted in a substantial reduction in the area of Kappaphycus alvarezii cultivation in Morowali Regency, decreasing from 78,420 ha in 2011 to 8,410 ha in 2014. Data from the Central Sulawesi Provincial Fisheries Service reveals a significant decline in dry Kappaphycus sp production from 2016-2020, reaching 383,360 – 59,129 tons/year, with no production expected in 2021. Similarly, E. spinosum and Gracilaria sp production have also experienced declines from 2018-2021. The results of the research show that the nickel content in the thallus of seaweed along the Morowali waters is very high and can be dangerous and is thought to be the cause of the extinction of the seaweed. Keywords: Seaweed, Mining, Exploitation, Extinction